Cultural elements underlying the community health representative – client relationship on Navajo Nation. Issue 1 (December 2017) - Gampa, Vikas; Smith, Casey; Muskett, Olivia; King, Caroline; Sehn, Hannah; Malone, Jamy; Curley, Cameron; Brown, Chris; Begay, Mae-Gilene; Shin, Sonya; Nelson, Adrianne
Abstract Background Navajo Nation Community Health Representatives (CHR) are trained community health workers (CHWs) who provide crucial services for patients and families. The success of the CHRs' interventions depends on the interactions between the CHRs and their clients. This research investigates the culturally specific factors that build and sustain the CHR-client interaction. Methods In-depth interviews were conducted with 16 CHRs on Navajo Nation. Interviews were transcribed and coded according to relevant themes. Code summaries were organized into a narrative using grounded theory techniques. Results The analysis revealed four findings critical to the development of a CHR-client relationship. Trust is essential to this relationship and provides a basis for providing quality services to the client. The ability to build and maintain trust is defined by tradition and culture. CHRs must be respectful of the diverse traditional and social practices. Lastly, the passing of clients brings together the CHR, the client's family, and the community. Conclusion Understanding the cultural elements of the CHR-client relationship will inform the work of community partners, clinical providers, and other indigenous communities working to strengthen CHR programs and obtain positive health outcomes among marginalized communities.